International Agricultural Research Center Director Preferences for an Information Department Head; Radio Tape User Survey - Everett Metcalf; James F. Whitman (Journal of Applied Communications, 1981)
Two research briefs: International Agricultural Research Center Director Preferences for an Information Department Head by Everett Metcalf; Radio Tape User Survey by James F. Whitman